Ruth Gordon papers - Gordon, Ruth, 1896-1985.
Correspondence, scripts, screenplays, box office statements, production material, reviews, financial records, biographical material, and other papers relating chiefly to the plays and motion pictures in which Gordon appeared. Includes scripts of The Loves of Cass McGuire, A Very Rich Woman, and Years Ago; screenplays of The Actress, Lord Love a Duck, Rosemary's Baby, and What Ever Happened to Aunt Alice?; and records pertaining to The Matchmaker and other plays. Correspondents include Edna Ferber, Alec Guinness, Vivien Leigh, Anita Loos, and Robert Morse.
Library of Congress Prints and Photographs Division.
Actress and playwright.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ferber, Edna, -- 1887-1968 -- Correspondence; Guinness, Alec, -- 1914-2000 -- Correspondence; Leigh, Vivien, -- 1913-1967 -- Correspondence; Loos, Anita, -- 1893-1981 -- Correspondence; Morse, Robert, -- 1931- -- Correspondence; Drama -- Stories, plots, etc; Motion picture plays, American; Motion pictures; Theater; Actresses; Playwrights